Causes of Transfer of Neonates (Born after ≥34 Weeks of Gestation) to the Neonatal Intensive Care Unit Owing to Respiratory Distress and their Clinical Features - Yu Jin Jung (Korean Society of Neonatology, 2018)
Purpose Respiratory morbidity is the most common problem among neonates admitted to neonatal intensive care units. Therefore, the aim of this study was to make a differential diagnosis between transient tachypnea of the newborn (TTN), respiratory distress syndrome (RDS), and pneumonia through comparison of clinical features and test results. Methods This retrospective study was conducted in 86 infants with TTN, RDS, or pneumonia. These were infants who had respiratory distress, were born after ≥34 weeks of gestation, and transferred to the neonatal intensive care unit of Kosin University Gospel Hospital between June 1, 2011 and June 30, 2016. Results The numbers (percentage) of infants with TTN, RDS, and pneumonia were 51 (59.3%), 20 (23.3%), and 15 (17.4%), respectively. Late-preterm and early-term newborns accounted for 65.1% of the infants. Tachypnea was observed in 74.4% of the neonates. The median age at admission was 4 hours (0 to 116) after birth. The infants with RDS had significantly lower birth weights, pH levels, base excess and oxygen saturation levels at admission, longer duration of total ventilator therapy, and hospital stay than those in the other two groups. The infants with pneumonia showed significantly high initial highsensitivity C-reactive protein levels and significant chest radiographic findings. Conclusion Early differential diagnosis for TTN, RDS, and pneumonia is challenging because they show similar respiratory symptoms at an early stage. Clinical features and test results can be used to determine the etiology of respiratory distress and early antibiotic treatment.